Climate Change and Resource Conflicts in Northeast and North Central Nigeria: Threats and Responses - Duyile, Praise Fisayo; Gowon-Adelabu, Nenpomingyi Sarah (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
Climate change is increasingly recognized as a significant driver of resource-related conflicts, particularly in regions where natural resources are scarce and communities depend heavily on them. Nigeria, a resource-rich nation, has witnessed a rise in violent inter-communal conflicts, particularly in the North-Central region, where climate-induced constraints on land, water, and fodder access exacerbate tensions. This study investigates the impact of climate change on resource conflicts in Nigeria and evaluates the responses of both governmental and community-based efforts to mitigate these challenges. Employing a mixed-methods approach—including desk reviews, key informant interviews, and focus group discussions. This research reveals that climate change has intensified various forms of conflict, such as farmer-herder clashes and kidnappings, particularly in northern regions. The findings indicate that existing mitigation strategies are inadequate and lack long-term planning. To address these challenges effectively, the study advocates for an integrated, multi-stakeholder approach involving the government, community organizations, and the private sector to enhance sustainable resource management and conflict prevention. Furthermore, policymakers are urged to prioritize locally tailored climate adaptation measures, promote resilient livelihoods, and strengthen environmental governance to foster long-term stability in Nigeria.